The effects of Electronic Word of Mouth (eWOM) on the adoption of consumer eWOM information - Le-Hoang, Phuong Viet (2020)
The purpose of this research is to explore and test the effect of electronic Word-of-mouth (eWOM) on the adoption of consumer eWOM information. Through the credibility variables of the eWOM, namely the trust of the eWOM news source, the quantity of eWOM, the quality of eWOM and consumer expertise in the case of female consumers when buying cosmetics in Ho Chi Minh City, Vietnam. To achieve this goal, the author does conduct research by submitting an online survey questionnaire and obtained 200 valid questionnaires. The online questionnaire has targeted internet users, who have previously purchased online and read reviews online received from the provider's website. The result from Exploratory Factor Analysis (EFA) shows that consumer expertise has the most significant effect on consumer adoption of eWOM information while the number of eWOM has the least impact. Besides, the credibility of eWOM news sources and the quality of eWOM also indirectly affect the adoption of eWOM information. What is more, the study suggests some recommendations to cosmetic businesses so that they develop applications or websites where assessments and quality of information are relevant, and the current expertise of consumers is increasingly present.